Long-Term Exposure to Traffic-Related Air Pollution and Risk of Incident Atrial Fibrillation: A Cohort Study - Monrad, Maria (Environ Health Perspect, 2016)
BACKGROUND: Atrial fibrillation is the most common sustained arrhythmia and is associated with cardiovascular morbidity and mortality. The few studies conducted on short-term effects of air pollution on episodes of atrial fibrillation indicate a positive association, though not consistently. OBJECTIVES: The aim of this study was to evaluate the long-term impact of traffic-related air pollution on incidence of atrial fibrillation in the general population. METHODS: In the Danish Diet, Cancer, and Health cohort of 57,053 people 50–64 years old at enrollment in 1993–1997, we identified 2,700 cases of first-ever hospital admission for atrial fibrillation from enrollment to end of follow-up in 2011. For all cohort members, exposure to traffic-related air pollution assessed as nitrogen dioxide (NO(2)) and nitrogen oxides (NO(x)) was estimated at all present and past residential addresses from 1984 to 2011 using a validated dispersion model. We used Cox proportional hazard model to estimate associations between long-term residential exposure to NO(2) and NO(x) and risk of atrial fibrillation, after adjusting for lifestyle and socioeconomic position. RESULTS: A 10 μg/m(3) higher 10-year time-weighted mean exposure to NO(2) preceding diagnosis was associated with an 8% higher risk of atrial fibrillation [incidence rate ratio: 1.08; 95% confidence interval (CI): 1.01, 1.14] in adjusted analysis. Though weaker, similar results were obtained for long-term residential exposure to NO(x). We found no clear tendencies regarding effect modification of the association between NO(2) and atrial fibrillation by sex, smoking, hypertension or myocardial infarction. CONCLUSION: We found long-term residential traffic-related air pollution to be associated with higher risk of atrial fibrillation. Accordingly, the present findings lend further support to the demand for abatement of air pollution. CITATION: Monrad M, Sajadieh A, Christensen JS, Ketzel M, Raaschou-Nielsen O, Tjønneland A, Overvad K, Loft S, Sørensen M. 2017. Long-term exposure to traffic-related air pollution and risk of incident atrial fibrillation: a cohort study. Environ Health Perspect 125:422–427; http://dx.doi.org/10.1289/EHP392